Trans umbilical first trocar access during laparoscopic surgery - Resutra, Ritvik; Mahajan, Neha; Gupta, Rajive (International Journal of Research in Medical Sciences, 2019)
Background: In order to perform laparoscopic procedures, it is necessary to first access the peritoneal cavity and establish carbon dioxide pneumoperitoneum. The placement of the first trocar remains a critical step in laparoscopic surgery. In order to minimize complications associated with placement of first trocar, several techniques have been reported. Author describe a surgical technique that provides a quick, safe, and reliable initial access to the peritoneal cavity with its excellent functional and cosmetic results. Methods: Retrospective study of patients who underwent various laparoscopic procedures at Maxx lyfe Hospital, Bathindi, Jammu was carried out by the closed technique for initial access to the peritoneal cavity through the umbilicus from July 2016 to May 2019. In this study, patients who had a prior midline laparotomy with involvement of the umbilicus were excluded. Results: Authors analyzed 456 patients (M = 190; F = 266) in the study period. Average age of the patients was 32 years (range:12-86). A physiologic defect was identified in the umbilical region in all patients who had no history of previous abdominal surgery in that region. The average time to access the peritoneal cavity was 30 seconds (range: 20-50). Conclusions: This technique is quick, safe, reliable, simple, and easy to learn and easy to perform. It is associated with no mortality and minimal morbidity and has excellent cosmetic results. Based on authors experience, authors believe that this method provides surgeons with an effective and safe way to insert the first trocar and recommend it as a routine procedure to access the peritoneal cavity for abdominal laparoscopic surgery.